NILAI-NILAI ISLAMI DALAM MANAJEMEN MUTU TERPADU (MMT) PENDIDIKAN BERBASIS PERILAKU - Sodikin, Unang; Sa’diyah, Maemunah; Samsuddin, Samsuddin; Iskandar, Iskandar (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
This research article discusses the application of Islamic values in Integrated Quality Management (IQM) of behavior-based education, emphasizing the integration of Islamic principles in all aspects of educational management. This study is a library research with a qualitative approach, using content analysis methods to analyze documents presented analytically. The research findings indicate that behavior-based IQM in education, grounded in Islamic values, functions as a tool to achieve the vision of Islamic education in building a better civilization. Islamic values in IQM include tauhid as the foundation, akhlak as both the goal and process, justice as the pillar of balance, and responsibility and trust. This approach emphasizes the role of educators as role models and the creation of an Islamic school culture that supports the formation of noble character. Sincerity becomes the main motivation in education, with the goal of educating students for the sake of Allah's pleasure. Collaboration between teachers, parents, and the community is also crucial for the success of education, as well as the holistic development of individual potential